2000
DOI: 10.1093/gerona/55.4.m207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Psychosocial Impact of Urinary Incontinence in Older People of a Spanish Rural Population

Abstract: Urinary incontinence is a very frequent symptom in our population. Half the incontinent subjects suffer from some degree of psychosocial limitation. The volume of urine loss and being married are the most important factors with psychosocial impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Frequency (four levels) was multiplied by the amount of leakage (three levels). The resulting index values (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) were further categorized into slight, moderate, severe, and very severe ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequency (four levels) was multiplied by the amount of leakage (three levels). The resulting index values (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) were further categorized into slight, moderate, severe, and very severe ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, the ISI has been used in many different studies of UI, both epidemiological [5][6][7][8][9][10] and clinical [11][12][13][14][15][16], and it has received the highest recommendation from the 2nd and 3rd International Consultation on Incontinence [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The subjects in this comprehensive geriatric health examination survey were women randomly selected from the Basic Resident Register of 15,773 people aged 70 and older residing in Itabashi ward of Metropolitan Tokyo as of October 1,2002. A letter outlining the study and describing its objective, and the way that the personal data would be used was mailed to the people selected, inviting them to participate in the study.…”
Section: Study Populationmentioning
confidence: 99%
“…Studies have indicated that UI can have a significant negative effect on the lives of older people [10]. For example, it has been associated with troublesome symptoms such as aches, pain, weakness, and shortness of breath [11], as well as with an increased risk for outcomes such as falls and fractures [12, 13].…”
Section: Introductionmentioning
confidence: 99%